Personality and voting for a right-wing populist party: evidence from Switzerland - Ackermann, Kathrin; Zampieri, Eros; Freitag, Markus (Swiss political science review, 2018)
Many established democracies are currently challenged by populist parties and movements. Switzerland is a particularly interesting case because it has an established right-wing populist party that is part of the governmental coalition on a regular basis: the Swiss People's Party (SVP). We study the electoral success of the SVP from a psychological perspective and argue that dispositions captured by the Big Five personality traits are related to voting for the SVP. Analyzing data from the Swiss Electoral Study (Selects) 2015, we find support for a negative relationship between openness to experience and agreeableness and voting for the SVP as well as a positive relationship between conscientiousness and extraversion and voting for this right-wing populist party. Additional analyses indicate that attitudes toward immigration mediate these relationships to some degree. Agreeableness and conscientiousness are, however, still systematically related to voting for the SVP when attitudinal factors are controlled for.
Gesehen am 14.04.2021